Shakespeare & Hathaway : private investigators. Season three [videorecording (DVD)] - Thompson, Paul Matthew (BBC Studios : British Broadcasting Corporation, 2020)
Private investigators Frank Hathaway and Luella Shakespeare continue their work investigating murder, kidnap, blackmail and infidelity in the English town of Stratford-upon-Avon.